How Does the Southern Annular Mode Control Surface Melt in East Antarctica? - Dominic Saunderson; Andrew N. Mackintosh; Felicity S. McCormack; Richard S. Jones; Christiaan T. vanDalum (Geophysical Research Letters)
Abstract Surface melt in East Antarctica is strongly correlated with the Southern Annular Mode (SAM) index, but the spatiotemporal variability of the relationship, and the physical processes responsible for it, have not been examined. Here, using melt flux estimates and climate variables from the RACMO2.3p3 regional climate model, we show that a decreasing SAM index is associated with increased melt in Dronning Maud Land primarily owing to reduced precipitation and greater absorption of solar radiation. Conversely, in Wilkes Land, a decreasing SAM index corresponds to increased melt because of greater incoming longwave radiation from a warmer atmosphere. We also demonstrate that SAM‐melt correlations are strongest in December as the melt season develops, and that the SAM’s influence on peak melt intensities in January occurs indirectly through the snowmelt‐albedo feedback. Future work must account for such variability in the physical processes underlying the SAM‐melt relationship to reduce uncertainty in surface melt projections.